Four new species of Hexactinellida (Porifera) and a name replacement from the NE Pacific - Reiswig, Henry M. (Zootaxa, 2018)
Four new species of Hexactinellida are described from the northwest coast of North America. Two northern ones from bottom longline sablefish traps set on Bowie Seamount off northwest Canada are Pinulasma bowiensis and Rhabdocalyptus trichotis. Two southern forms picked by ROV from the wreck of USS Independence off San Francisco, California are Staurocalyptus pamelaturnerae and Hyalascus farallonensis. A fifth specimen from the southern site is considered conspecific with the junior homonym Farrea aculeata Schulze, and allowed renaming of that species as Farrea schulzei. These additions bring the number of Hexactinellida known from the area (30º–90º N) to 62 species.